A self‐packaged wideband filtering power divider based on substrate‐integrated suspended line. Issue 2 (11th November 2019) - Yang, Jiale; Qiu, Gongan; Xu, Kai; Shi, Jin; Yang, Yongjie
Abstract: In this study, a filtering power divider (FPD) is proposed by utilizing one T‐shaped tri‐mode stepped‐impedance resonator with input/output coupling structures based on substrate‐integrated suspended line (SISL). The circuit topology and SISL technology are combined together to reach balance in performances such as compact size, wideband, high frequency selectivity, low loss, good in‐band isolation, wide stopband, and self‐packaging so that there are no obvious flaws. Wide bandwidth and two near‐band transmission zeros are contributed by the proposed circuit topology. Good isolation can be obtained by comparing different coupling schemes with one resistor. An additional transmission zero for extending the upper stopband can be achieved by the two closely placed stubs without increasing the size of the design. Low loss and self‐packaging can be realized by SISL technology. For demonstration, a prototype is implemented with the size of 0.5 λ g  × 0.28 λ g, which exhibits the 1‐dB fractional bandwidth of 26.3%, the frequency selectivity of 0.25/0.37 at the lower/upper edges of the passband, and the insertion loss of 1.1 dB (including transition) at the center frequency ( f 0 ) of 3.34 GHz, while the in‐band isolation is higher than 20 dB and the 15‐dB stopband is achieved up to 3.74 f 0 .